COLLABORATIVE GOVERNANCE DALAM PENGEMBANGAN DESA WISATA BUDO KABUPATEN MINAHASA UTARA - Onibala, Nancy Melisa; Tendean, Noudy R.P; Alhasni, Rahma A (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2024)
The development of a tourist village is expected to be equitable in accordance with the concept of sustainable tourism development. Tourism potential exists in Budo village in the form of natural tourism in the form of beaches, underwater and mountains; Cultural Tourism in the form of arts, customs and traditional culinary; Educational Tourism in the form of mangrove forests and underwater potential. Budo village also has handicrafts in the form of Ginto crafts that can be used as souvenirs typical of Budo village. The community has also prepared a home stay for visiting tourists. Collaborative governance is something interesting to study in the development of Budo tourism village, because it involves various local government organisations, Kerta village community, private sector and others. This research uses a qualitative method with a descriptive approach through determining informants using non-probability sampling techniques by purposive sampling.  The results of this study are where the management of Budo Tourism Village still only relies on the community, the contribution of the government and the private sector is still minimal. So it still needs to be improved again for the role of other stakeholders.